Dinamika Ovarium pada Kuda Hasil Persilangan Pejantan Thoroughbred dengan Induk Lokal Indonesia - Muhammad Danang Eko Yulianto; Bambang Purwantara; Amrozi Amrozi (Buletin Peternakan, 2016)
The development of horse breeding industry in Indonesia was commenced through horse racing events held all over the country. It were accelerated by the development of Thoroughbred-Indonesian local Crossbred horses. There are many broodmares injured during their racing time and retired from the racetracks. They may still has a reproductive vigor to continue on producing offsprings. Very little information has been reported on the monitoring the reproductive capacity of the mares. The objective of this study was to explore ultrasonography imaging of the ovarian dynamics, correlated with the estrus behavior of the Thoroughbred-Indonesian local crossbred mares. Three Thoroughbred-Indonesian local crossbred mares with 6.25-12.5% of local genetics aged 12-20 years old were used in this study. Estrus and ovulation were synchronized by 10 mg PGF2α i.m. at luteal phase and 1,500 IU hCG i.m. injection when the dominant follicle reach ≥30 mm in diameter. Ultrasonography examination was done every morning at approximately at the same time. Estrus behavior was observed by using teaser stallions following a standard method. Results of the experiment indicated that onset of the estrus was reached 1.33±0.58 days after the hCG injection, with the average duration of 4.00±1.00 days. The ovulations were done at 5.33±1.15 days after PGF2α treatment and 66.67±10.07 hours after hCG treatment. Maximum follicle diameter was identified to reach 4.50±0.52 cm at one day before ovulation. The mares performed 25.4±3.38 days length of estrus cycle with 2-3 follicular  waves. It had been identified that the estrus duration  was  6.8±1.92  days  in mares with the age of 12-20 years. The average of maximum diameter of the largest follicle before ovulation was 4.2±1.24 cm. In conclusion, to improve the efficiency of breeding, several information are needed i.e. the optimal time of ovulation, relevan parameters related to follicular development.